2012
DOI: 10.15578/ifrj.18.1.2012.19-33
|View full text |Cite
|
Sign up to set email alerts
|

Developing Recommendations for Undertaking Cpue Standardisation Using Observer Program Data

Abstract: Abundance indices based on nominal CPUE do not take into account confounding factors such as fishing strategy and environmental conditions, that can decouple any underlying abundance signal in the catch rate. As such, the assumption that CPUE is proportional to abundance is frequently violated. CPUE standardisation is one of the common analyses applied. The aims of this paper were to provide a statistical modelling framework for conducting CPUE standardisations using the Observer Program data for bigeye tuna, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
2
15
0
7
Order By: Relevance
“…The result is expected to support ALB management study in Eastern Indian Ocean and update the information which was previously reported by Sadiyah et al (2012).…”
Section: Standardizing Cpue Of Albacore Tuna (Thunnus Alalungasupporting
confidence: 85%
See 3 more Smart Citations
“…The result is expected to support ALB management study in Eastern Indian Ocean and update the information which was previously reported by Sadiyah et al (2012).…”
Section: Standardizing Cpue Of Albacore Tuna (Thunnus Alalungasupporting
confidence: 85%
“…Temporal trends of nominal CPUEs were much influenced by different factors which associated with fishing practice and environmental condition (Sadiyah et al, 2012). The different factor such as time of fishing (year), season, fishing area and hook between float (HBF) can cause an extreme value in nominal CPUE time series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside of operational factors used in this analysis, Sadiyah et al (2012) reported that year, area and bait factors significantly influenced the nominal CPUEs of tuna known as technological creep. However, this study did not discuss about those factors and mainly focused on operational aspects related to the CPUE.…”
Section: Discussionmentioning
confidence: 99%